Pengaruh Kebisingan terhadap Ambang Pendengaran Karyawan Arena Bermain - Septianingsih, Cintia P.; Palandeng, Ora Et Labora I.; Pelealu, Olivia C. P. (Universitas Sam Ratulangi, 2020)
Abstract: Noise at a certain level and time can cause human health problems and environmental discomfort. These conditions occur if the noise intensity exceeds the threshold level related to time and place. This study was aimed to obtain the influence of noise intensity at work to hearing disturbance among the employees of game arenas. This was an analytical study with a cross-sectional design. Data were obtained by questionnaire filling, noise measurement by using a sound level meter, physical examination, and auditory function examination by using audiometry and then were analyzed by using the Fisher exact test. There were three game arenas in this study, as follows: Amazing Zone Star Square Manado, Amazone, and Timezone Manado Town Square. The results showed that there were 18 respondents in this study. The mean noise intensity at the game arenas were 85.5 dBA at Timezone, 89.8 dBA at Amazone, and 85.4 dBA at Amazing Zone. Hearing disturbance was found ian 72% of the total employees. The Fisher exact test showed a p-value of 0.294 (p>0.05) for the influence of noise intensity to hearing disturbance. In conclusion, the noise intensity at the game arenas did not affect the hearing threshold of the game arena employees.Keywords: noise, hearing threshold, playing area employeesÂ Abstrak: Kebisingan dalam tingkat dan waktu tertentu dapat menimbulkan gangguan kesehatan manusia dan kenyamanan lingkungan. Hal ini terjadi jika intensitas bising melebihi nilai ambang batas yang ditetapkan berdasarkan waktu dan tempatPenelitian ini bertujuan untuk mendapatkan hubungan antara intensitas kebisingan di tempat kerja dengan gangguan fungsi pendengaran pada karyawan arena bermain. Jenis penelitian ialah analitik dengan desain potong lintang. Data diperoleh melalui pengisian kuisioner, pengukuran kebisingan dengan sound level meter, pemeriksaan fisik, dan pemeriksaan fungsi pendengaran dengan audiometri. Analisis data menggunakan uji Fisher exact. Terdapat 3 arena bermain yang diikutsertakan dalam penelitian ini, yaitu: Amazing Zone Star Square Manado, Amazone, dan Timezone Manado Town Square. Hasil penelitian mendapatkan intensitas kebisingan arena bermain sebagai berikut: Timezone 85,5 dBA, Amazone 89,8 dBA, dan Amazing Zone 85,4 dBA. Gangguan pendengaran didapatkan pada 72% dari total responden. Hasil uji Fisher exact mendapatkan nilai p=0,294 (p>0,05) untuk pengaruh kebisingan terhadap gangguan pendengaran. Simpulan penelitian ini ialah kebisingan di arena bermain tidak memengaruhi ambang pendengaran karyawan arena bermain.Kata kunci: bising, ambang pendengaran, karyawan arena bermain